Current Conditions and Opportunities of Biofarming in Hungary - Nagy, Petra (Acta Agraria Debreceniensis, 2004)
The aim of organic farming is not to maximize income, but to achieve optimal product quality. It is completed by the tightest possible material, and energy flow within the farm. Organic agriculture significantly reduces external inputs by avoiding the use of chemo-synthetic fertilizers, pesticides and pharmaceuticals. Instead it works with nature to increase both agricultural yields and disease resistance. Total independence of external resources can not be achieved in Hungary due to the small-scale of organic animal husbandry. Some materials in limited quantities can be purchased from external resources, though the group of these materials is strictly regulated. Organic farming harmonizes with the concept of European multifunctional agriculture, because besides farming, it includes social considerations, as it helps to maintain natural resources and the relationship between people and their environment, and provides a living for those living in the region. As regards organic farming the fertility of the soil and the health of vegetation can be influenced in various ways. Farmers have to be highly skilled and able to manage a farm with great expertise. Generally it can be stated that as the use of non-organically produced products is limited, the opportunities to correct failures made by the farmer are minimal, contrary to conventional farming. Farmers must be intent on developing the tightest material- and energy flow. This means that organic farms ideally have both animal husbandry and crop production. This energy and skill demanding system of farming is compensated by state subsidies, growing market share and relatively high prices for organic products.